Financial development and income inequality - Sebastian Jauch; Sebastian Watzka (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze the link between financial development and income inequality for a broad unbalanced dataset of 138 developed and developing countries over the years 1960 to 2008. Using credit-to-GDP as measure of financial development, our results reject theoretical models predicting a negative impact of financial development on income inequality measured by the Gini coefficient. Controlling for country fixed effects and GDP per capita, we find that financial development has a positive effect on income inequality. These results are robust to different measures of financial development.
Keywords: O15; O16; 330; financial development; income inequality; Finanzsektor; Entwicklung; Einkommensverteilung; Schätzung; Entwicklungsländer; Industriestaaten